2019
DOI: 10.4103/aian.aian_492_18
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of human leukocyte antigen B*15:02 screening in severe carbamazepine hypersensitivity syndrome

Abstract: Background:Despite many studies suggesting an association between human leukocyte antigen (HLA)-B*15:02 and carbamazepine (CBZ)-induced severe cutaneous adverse drug reactions essentially toxic epidermal necrolysis (TEN) and Stevens–Johnson syndrome (SJS), the evidence of association in different populations and the degree of association remain uncertain.Materials and Methods:The primary analysis was based on population control studies. Data were pooled by means of a random-effects model, and sensitivity, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Combining this result with previous studies, 100 the authors suggest that screening two alleles, HLA‐B*57:01 and HLA‐A*31:01, could reduce CBZ‐induced‐SCAR in Europeans 99 . HLA‐B*15:02 has also been strongly associated with CBZ‐induced‐SJS/TEN in other ethnic groups such as Han Chinese, Thai, and Malaysian populations 101 . These results suggest that screening this allele in populations with high allele frequency could prevent the occurrence of CBZ‐induced‐SJS/TEN 101 …”
Section: Genetic Susceptibilitysupporting
confidence: 71%
See 1 more Smart Citation
“…Combining this result with previous studies, 100 the authors suggest that screening two alleles, HLA‐B*57:01 and HLA‐A*31:01, could reduce CBZ‐induced‐SCAR in Europeans 99 . HLA‐B*15:02 has also been strongly associated with CBZ‐induced‐SJS/TEN in other ethnic groups such as Han Chinese, Thai, and Malaysian populations 101 . These results suggest that screening this allele in populations with high allele frequency could prevent the occurrence of CBZ‐induced‐SJS/TEN 101 …”
Section: Genetic Susceptibilitysupporting
confidence: 71%
“…HLA‐B*15:02 has also been strongly associated with CBZ‐induced‐SJS/TEN in other ethnic groups such as Han Chinese, Thai, and Malaysian populations 101 . These results suggest that screening this allele in populations with high allele frequency could prevent the occurrence of CBZ‐induced‐SJS/TEN 101 …”
Section: Genetic Susceptibilitymentioning
confidence: 90%
“…Regarding global populations, Southeast Asians are regarded as having the highest frequency of HLA-B*15:02 in the world ( Moutaouakkil et al, 2019 ; Van Nguyen et al, 2019 ). Indeed, numerous studies published the frequency of HLA-B*15:02 in their own country, such as 15.11% in Thailand ( Zhang et al, 2011 ), 32.8% in Indonesia ( Khosama, 2017 ), 8.3% in Malaysia ( Chang et al, 2011 ), and 5.7% in Singapore ( Middleton et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Caucasians, Japanese, and Koreans, even though a myriad of meticulous research has been conducted about HLA-B*1502 , this allele is reported to be rare and not associated with statistically significant risk in these populations. In contrast, the HLA-B*15:02 allele was believed to have the highest allele frequency and fatal risk in the general population of Southeast Asia ( Moutaouakkil et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each antiepileptic was analyzed separately. For Carbamazepine, there were 42 case-control studies(11-14)(15-52)and 7 meta analyses (39,(53)(54)(55)(56)(57)(58). For Lamotrigine, there were 30 case-control studies (13,15,17,26,34,39,42,46,49,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) and 3 meta-analyses (66,68,70).…”
Section: Study Characteristicsmentioning
confidence: 99%